PERLINDUNGAN HUKUM TERHADAP KORBAN KEKERASAN DALAM RUMAH TANGGA BERDASARKAN UNDANG-UNDANG NOMOR 23 TAHUN 2004 - Maulana, Adam Hamka; Cornelis, Vieta Imelda; Hamdani, Fathul (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
This study aims to analyze the concept of legal protection for women victims of domestic violence based on Law Number 23 of 2004 concerning the Elimination of Domestic Violence, as well as to identify the factors that influence the effectiveness of the implementation of such legal protection in Indonesia. This research employs a normative juridical approach with qualitative analysis. The results show that legal protection for women victims of domestic violence has been comprehensively regulated in the Domestic Violence Law, covering emergency protection mechanisms, psychosocial recovery, and legal assistance services. However, its effectiveness remains hampered by several factors, including weak law enforcement, entrenched patriarchal culture, limited victim support infrastructure, and low legal literacy among women. Therefore, synergistic efforts from the state, society, and law enforcement officials are needed to realize holistic and equitable legal protection